(untitled) (Kerala Journal of Psychiatry, 2024)
Background Alcohol dependence syndrome (ADS) is one of the most well-known issues in the public domain; it affects not only the patient but also those in their immediate vicinity, including family members. Family members may eventually become codependent, which throws off the dynamics within the family. Recognizing and rectifying this issue will, in turn, improve their coping strategies and enhance their quality of life. This study analyses the codependency and personality traits of caregivers of ADS patients and evaluates the association between these two variables. Methods This cross-sectional study was conducted in the Psychiatry department of a tertiary care facility in Kerala, India. For this study, 92 male ADS patients’ caregivers were evaluated. The International Personality Disorder Examination (IPDE) and the Spann-Fischer Codependency Scale (SFCS) assessed caregivers’ personality traits and codependency. The collected data was examined, and the Fisher’s Exact test was used to determine the statistical significance. Results The SFCS ratings of 92 caregivers of ADS patients showed that 57.61% had low, 29.35% had moderate, and 13.04% had severe codependency. An IPDE personality examination revealed that 29.3% of caregivers had anxious characteristics, and 30.4% had dependent personality traits. A p-value of <0.001 indicated a statistically significant association between codependency and personality traits. Conclusion In this study, a statistically significant association between codependency and personality traits among caregivers of ADS patients was observed. Funding: Self funded Conflict of Interest: None